Bovine leukosis and the possibility to cause cancer in humans: A scientific review - Alabbody, Huda Hameed Kadhim (The Iraqi Journal of Veterinary Medicine, 2018)
This review was made to explore the recent multiple studies on enzootic bovine leukosis, focusing on its prevalence, economic impact, the link with public health and the possibility to cause cancer in humans. The causative agent of enzootic bovine leukosis is a virus closely related to human T- cell leukemia virus (HTLV-1). The closeness between the two viruses helps the progress of cancer research in diagnosis and treatment, also the development of a vaccine in both human and veterinary medicine .The enzootic bovine leukosis is widely spread in the continents. The economic loses of enzootic bovine leukosis is related to the lowered productivity of effected cattle, morbidity, mortality and cost of control and eradication. This review proved that bovine leukemia virus is innocent from human cancer infection and there is no proof of virus living in human tissues. But this subject needs a lot of research to know the mechanism of the virus and its affects in cellular content of the organism.